Changes in runoff from major alpine watersheds on the Qinghai-Tibetan plateau: A review - Guohui Li; Zongxing Li; Baoqing Zhang; Zongjie Li (Journal of Hydrology: Regional Studies)
Study region: The Qinghai-Tibetan Plateau (QTP). Study focus: Water resources in QTP are increasingly vulnerable to climate change, yet comprehensive understanding of runoff dynamics and their drivers remains limited. This study systematically evaluates: (1) shifts in runoff recharge mechanisms under climate warming, (2) the relative contributions of precipitation, groundwater, and cryospheric meltwater to runoff generation, and (3) the differential impacts of climate change versus anthropogenic activities on hydrological processes. New hydrological insights: (1) Rainfall dominates runoff generation in most high-elevation watersheds when only precipitation and snowmelt inputs are considered, while groundwater contributes significantly to runoff generation in specific watersheds (e.g., SLR, YAR) during certain periods when groundwater inputs are added for consideration. (2) Runoff depths generally increased, though localized declines occurred in some Riverside Corridor basins, coinciding with cryospheric retreat and altered precipitation regimes. (3) Climate change surpassed anthropogenic factors as the primary driver of streamflow changes in the SLR and YER basins from the mid-20th to early 21st century, highlighting a regional tipping point in hydrological controls. The findings underscore the vulnerability of the Plateau’s water resources to warming and advocate for basin-specific adaptive management strategies.